Perlindungan Hukum Pekerja Perempuan Sektor Informal - Triana Sofiani (MUWAZAH : jurnal kajian gender, 2017)
This paper examines the legal protection of informal women workers, who until now have not received legal protection. The condition occurs because the ideology that is built leads to the effort of marginalization of women, so that in their working relationship experience exploitation. For example: unclear working rules; a disproportionate wage system; no social and health insurance and so on. Act of the Republic of Indonesia Number 13 Year 2003 concerning Manpower, can actually be made as legal umbrella for informal women workers, because they are included in the category of labor as well as status as workers / laborers as contained in the Manpower Act. However, the absence of the government's political will to recognize informal sector workers, as workers, leaves them out of labor protection law.